Psychotherapy and first-year university psychology student perspectives on personal therapy: An analytical interpretation - Zhou, Ran; Sumettikoon, Piyapong (My University, 2025)
Psychotherapy plays a pivotal role in addressing the multifaceted challenges of mental health by offering diverse approaches to understanding and managing psychological disturbances. This research programme seeks to explore the perspectives, insights, and experiences of first-year psychology students regarding personal therapy. By focusing on this specific group, the study aims to investigate their understanding of psychotherapy and its critical contribution to fostering the psychological well-being of university students. Through qualitative analysis, the research identifies themes related to the importance of personal therapy in supporting the professional development of mental health practitioners in training. The findings not only illuminate the psychotherapeutic culture among university students but also carry significant implications for enhancing supportive frameworks and psychotherapeutic interventions within university settings, thereby improving student welfare and academic performance.
Keywords: First-Year University Students; Mental Health; Personal Therapy; Psychotherapy